2002
DOI: 10.1248/bpb.25.1467
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Hydrogen Peroxide Levels Caused by Coffee Drinking.

Abstract: Experiments with volunteers in Singapore have demonstrated that coffee drinking increases urinary hydrogen peroxide levels (Long, Halliwell, Free Rad. Res., 32, 463-467 (2000)). We re-examined the effect of coffee drinking of healthy Japanese subjects on urinary hydrogen peroxide levels. A cup of brewed or canned coffee commercially available in Japan generated 120-420 m mmol hydrogen peroxide in incubation in a neutral medium at 37°C for 6 h. The increased levels were higher than those obtained from a cup of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…(increasing the pH), which moves the equilibrium to the right. Although the oxidation of catechol can also be due to the transition metals such us Cu and Fe [38] [32,33], myricetin [31] and theaflavin-3 0 3 0 -digallate [39], while it enhances the accumulation of H 2 O 2 induced by para-aminophenol [17] and canned coffee [22]. In this context, it should be underlined that the reactions behind the H 2 O 2 -releasing activity of 3,4-DHPEA may be particularly complex and deeply influenced by the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…(increasing the pH), which moves the equilibrium to the right. Although the oxidation of catechol can also be due to the transition metals such us Cu and Fe [38] [32,33], myricetin [31] and theaflavin-3 0 3 0 -digallate [39], while it enhances the accumulation of H 2 O 2 induced by para-aminophenol [17] and canned coffee [22]. In this context, it should be underlined that the reactions behind the H 2 O 2 -releasing activity of 3,4-DHPEA may be particularly complex and deeply influenced by the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some study reported that urinary H 2 O 2 level was influenced by coffee drinking. 15 To avoid the bias effect of drink and foods, patients were fasting at least 8 hours before taking their urine and blood. The concentration of urinary H 2 O 2 in both groups were not a significant difference.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…In general, healthy smooth muscle is quite resistant to exogenous H 2 O 2 . The most extreme example is agonist activated bladder smooth muscle (bladder concentrations of H 2 O 2 often reach levels of 0.2-0.4 mM in healthy adults (21), which was shown to exhibit an EC 50 for relaxation of 36 mM H 2 O 2 (22)). Airway smooth muscle, although considerably more sensitive than bladder, still requires nearly mM concentrations of H 2 O 2 for relaxation of agonist induced contraction (23).…”
mentioning
confidence: 99%